Preparation of Football League Table and School Mathematics Teaching and Learning - Idehen, Festus (NIU Journal of Social Sciences; Vol 7 No 3 (2021): KIU Journal of Social Sciences, Vol. 7 No. 3, September 2021, 2021)
The purpose of this study was to assess preservice mathematics teachers' use of mathematical knowledge and skills to read, prepare and interpret football league table. The study combined both quantitative (performance test and questionnaire instrument) and qualitative (semi-structured interview instrument) methods. The research data were collected from 43 undergraduate preservice mathematics teachers. The instruments for the study were the Basic Mathematical knowledge and skills (BMFLT) test and the Semi-structured Interview (SSI) guide on reading, preparing and interpreting football league table. Six research questions were raised to guide the study and two of them were hypothesized. Frequencies, percentages, mean and standard deviation were used to answer the research questions and the t-test statistic was used to test the hypotheses. Results show that the level of performance of preservice mathematics teachers is high in the four mathematical areas of reading, solving problems, making inferences from and preparing football league table. That counting, addition, subtraction, multiplication and division are basic mathematical knowledge and skills needed by preservice mathematics teachers in reading, preparing and interpreting football league table. There is no significant difference between the mean performance scores of male and female teachers and those who play and do not play football. The study concludes that the football league table is perceived by the preservice mathematics teachers to be relevant and valuable to school mathematics teaching practices. It is recommended that student centered culturally responsive mathematics teachers' development programme and teaching methods/strategies should be promoted through the application of real life situations and examples. Keywords: Mathematics Teachers' Assessment, Basic Mathematical Knowledge and Skills, Preparation of Football League Table, Culturally Responsive Mathematics Education